Structure, ecological spectra and species dominance in riparian forests from Benin (West Africa) - Natta, Armand; YEDOMONHAN, HOUNNANKPON; ADOMOU, ARISTIDE COSSI; AGBANI, Pierre O.; SINSIN, Brice; AKOEGNINOU, Akpovi E.; VAN DER MAESEN, L. J. G. (My University, 2012)
This paper investigates the structure of the Benin Riparian Forests (RFs) through different methods: life forms, phytogeographic types, diameter class distribution, basal area, and stem density. Field data was collected in 373 phytosociological relevés using the Braun-Blanquet approach. RFs displayed a physiognomy that is highly variable in terms of structural characteristics. RFs in Benin were similar to many dense tropical forests and to the West African ones in particular, in terms of phytogeographical types (higher contribution of Guineo-Congolian basin species) and life forms (high abundance of phanerophytes and lianas, high occurrence of therophytes and medium size trees, low percentage of megaphanerophytes and woody lianas). Diameter class distribution was reserve J type, while values of basal area and stem density varied from 23 to 59 m2/ha, and 253 to 785 trees/ha respectively. Species dominance, in terms of abundance and basal area (i.e. 4.4% of the tree richness contributes 48.5% of overall abundance and 57.4% of the total basal area), was a major characteristic of RFs in Benin. The most dominant and frequent tree species were Pterocarpus santalinoides, Cola laurifolia, Syzygium guineense, Dialium guineense, Berlinia grandiflora, Cynometra megalophylla, Elaeis guineensis, Diospyros mespiliformis, Uapaca togoensis and Parinari congensis. Many stands of RFs are facing various levels of structural and floristic simplification, which include transformations in vegetation physiognomy, from dense pristine stands to sparsely forested waterways banks, riparian scrub, or bare land. Measures have to be taken to conserve the structural complexity of these edaphic and topographic forest ecosystems.
Keywords: Riparian forests; structure; dominance; Benin